A proposal for monitoring the process of internalization following Galperin's conception - Rivera Valdez, Leonardo Daniel; López Cortés, Vicente Arturo; García Flores, Marco Antonio (Frontiers in Psychology, 2023)
Since the era of Piaget and Vygotsky, private speech (PS) has been widely discussed, but in recent years, the avenues for its study have greatly expanded. In this study, we explored the use of a recoding scheme for PS inspired by the studies of Pyotr Galperin. A coding scheme for social speech, PS, and the lack of speech, as the form of action (FA) has been proposed (i.e., external social speech, external audible speech, inaudible speech, and mental FA when no speech was produced). An exploratory study was conducted to elucidate the appropriateness of the coding scheme, both ontogenetically and during tasks. The results showed that both the coding scheme by type of speech and FA were adequate for differentiating ontogenetically between children. However, only the coding schemes of the FA were appropriate for differentiating between children as a function of their performance (i.e., time and scores) in a Tower of London task. Moreover, Galperin's scheme was more suitable when there was redundancy in performance between those with audible and inaudible external speech.